2010
DOI: 10.1111/j.1440-1681.2010.05363.x
|View full text |Cite
|
Sign up to set email alerts
|

Clinical characteristics and mid‐term outcomes of acute myocardial infarction patients with prior cerebrovascular disease in an Asian population: Lessons from the Korea Acute Myocardial Infarction Registry

Abstract: 1. The aim of the present study was to evaluated the impact of prior cerebrovascular disease (CVD) on the clinical characteristics and mid-term clinical outcomes of patients with acute myocardial infarction (AMI) in the era of drug-eluting stents. 2. Data from 12 914 patients with acute myocardial infarction who were enrolled in the Korea Acute Myocardial Infarction Registry were analysed retrospectively from November 2005 to December 2007. Prior CVD was defined as having had one or more events of ischaemic or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 15 publications
0
15
0
Order By: Relevance
“…Most previous studies of patients with prior stroke undergoing PCI have focused on patients with acute MI, or only discussed the in‐hospital and short‐term prognosis . In the current study, all patients undergoing PCI, including those with ACS and stable CHD, were consecutively enrolled, which reflects the situation in the real world.…”
Section: Discussionmentioning
confidence: 99%
“…Most previous studies of patients with prior stroke undergoing PCI have focused on patients with acute MI, or only discussed the in‐hospital and short‐term prognosis . In the current study, all patients undergoing PCI, including those with ACS and stable CHD, were consecutively enrolled, which reflects the situation in the real world.…”
Section: Discussionmentioning
confidence: 99%
“…The design of the KAMIR study has been previously described. 15,16 Briefly, it is a Korean prospective multicentre online registry designed to reflect the 'real world' practice in Korean AMI patients in the drug-eluting stents (DES) era that was established with support from the Korean Circulation Society in November 2005. Forty-one major cardiovascular centres have registered details of AMI patients via the website (http://www.kamir.or.kr, accessed 31 August 2008).…”
Section: Methods the Kamir Studymentioning
confidence: 99%
“…A nationwide multicenter registry of AMI in Korea, the Korea Acute Myocardial Infarction Registry, was established in November 2005, and studies that have evaluated clinical characteristics and treatment outcomes of AMI patients in Korea have been reported (4, 5). Hong et al (6) analyzed data from the Korean National Health Insurance Database and reported time trends in the incidence of AMI in Korea from 1997 to 2007.…”
Section: Introductionmentioning
confidence: 99%